2016
DOI: 10.1016/j.jsha.2015.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C: A prognostic marker after myocardial infarction in patients without chronic kidney disease

Abstract: High cystatin C levels are associated with the severity of coronary artery disease in patients presenting an acute coronary syndrome and a normal renal function. Cystatin C is also associated to unfavourable cardiovascular outcomes during follow-up and appears as a strong predictor for risk of cardiovascular events and death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…Our concern study has shown that group with a high Cystatin C level is associated with significant in hospital mortality (P value 0.025), and also it is going with Leila Abid et al, 24 Which showed (P value 0.01 clinically significant). And another study where Cystatin C was used as a prognostic biomarker in STEMI and Shlipak et al 25 Eriksson et al have asserted that an increase in cholesterol or LDL-cholesterol levels are considered as risk factors of IHD, but CYS-C may reflect precisely the presence or absence of CAD.…”
Section: Discussionsupporting
confidence: 68%
“…Our concern study has shown that group with a high Cystatin C level is associated with significant in hospital mortality (P value 0.025), and also it is going with Leila Abid et al, 24 Which showed (P value 0.01 clinically significant). And another study where Cystatin C was used as a prognostic biomarker in STEMI and Shlipak et al 25 Eriksson et al have asserted that an increase in cholesterol or LDL-cholesterol levels are considered as risk factors of IHD, but CYS-C may reflect precisely the presence or absence of CAD.…”
Section: Discussionsupporting
confidence: 68%
“… 6 In addition, cystatin C has been shown to be useful for prognostic stratification in patients with ACS. 7 …”
Section: Introductionmentioning
confidence: 99%
“…Some serum markers of renal function filtered by the renal glomerulus such as beta-2 microglobulin (B2M) and cystatin C are thought to be more sensitive parameters for renal function assessment and stronger predictors for death and cardiovascular events compared to serum creatinine (SCr). [ 3 4 ] B2M is a polypeptide which is present on the surface of nucleated human cells and thrombocytes. [ 5 ] It has been viewed as a useful parameter for estimated glomerular filtration rate (eGFR) and detecting mild-to-moderate renal insufficiency.…”
Section: Introductionmentioning
confidence: 99%